UPACARA RITUAL SURAN SEBAGAI SARANA PELESTARIAN KESENIAN DI DUSUN TUTUP NGISOR, DESA SUMBER, KECAMATAN DUKUN, KABUPATEN MAGELANG - Aswoyo, Joko (Institut Seni Indoensia Surakarta, 2014)
This research is dedicated to reveal cultural phenomenon of the Suran sacred ceremony at a model forthe art perpetuation at village Tutu Ngisor, Sumber, district Dukun in Magelang. Suran is derivedfrom the word Suro as the first month of Javanese calendar. Suro month is identical to Muhharammonth in Hijjrah calendar. In the common Javanese society, it is believed that in the first month ofSuro (midnight Suro) they will have introspection of their selfness of doing activities nepi (finding aplace for keeping silent), kungkum (stand still inside of the water) and lek lekan (stay awake until inthe morning) in certain places like the peak of mountain, the estuary of river (tempuran) or sacredcemeteries. In the village of Tutup Ngisor, Sumber, district Dukun, Magelang, Suran is held in themiddle of month which is from 13-15 in the full moon. Suran in the village of Tutup Ngisor, Sumberdistrict Dukun, Magelang is supported by the society that has blood bound in one region. Suran inthe village of Tutup Ngisor , Sumber, disctrict Dukun, Magelang is as one of the art perpetuationmodel held by a community. The concept belongs to protection prevention, developing and dynamicusage.Giving all attention to the sacred ceremony in the village of Tutup Ngisor, Sumber districtDukun, Magelang, we find some factors that create art perpetuation. The factors are geographic site,supported society, natural surroundings, the figure of Romo Yoso Soedarmo at the pioneer art workshop,the ceremony continuity, the influence from all people like artists, cultural artists, and the publicfigure.The perpetuation of art in the village of Tutup Ngisor, Sumber, district Dukun , Magelang has impactfor the creativity and quantity of art living in another village around the village Tutup Ngisor, Sumber,district Dukun, Magelang. This research uses grounded theory approach. Grounded theory approachemphasizes the examination of behavior so this research does not take from a certain theory but fromthe data result to get a theory even it does not take from the reduced variables from a theory. Furthermore,the grounded theory research does not have to get influence from literature because it will stopcreativity in collection, understanding and analyzing the data.Keywords: Suran, art perpetuation